INCREASE OF INFORMATION TRANSPARENCY AS FACTOR OF THE SUSTAINABLE DEVELOPMENT OF THE RUSSIAN COMPANIES - V. Tumin; V. Makhalin; P. Kostromin (Вестник университета)
Indicators of activity of the companies are considered, administrative and organizational standards, their influence on information transparency of activity of the enterprises, a role of standards in a sustainable development are in details described. The maintenance of different types of the non-financial reporting as result of increase of information transparency, offers on her disclosure are formulated is analysed.